Perspectives and practices of Islamic Bank management in relation to stakeholders (Texas Journal of Multidisciplinary Studies, 2022)
This qualitative research aims to explore the perspectives, concepts, and management practices of Islamic financial institution management in relation to their stakeholders. Data were explored through indepth interviews. the respondents were managers of Islamic banks and Islamic microfinance institutions (baltul maal and tamvil) at various levels of government. This study showed that among the employees of the Islamic Bank, they have different but not in-depth and comprehensive knowledge about stakeholders. this perception was influenced by the level of education, the level of management, and the distribution of responsibilities. This has led management to have difficulty mapping and managing its stakeholders